Inflation Targeting in Iran - Bidabad, Bijan; Anaraki, Nahid Kalbasi (Asian Finance & Banking Review, 2019)
Inflation targeting in various forms has been adopted by a number of countries as a framework for making monetary policy more coherent and transparent and for increasing the credibility of monetary policy. Despite the language, referring to inflation target as the primary objective of monetary policy, central bankers always make room for short-run stabilization objectives, particularly with respect to output and exchange rate. Inflation targeting, in most cases, reduces the role of intermediate targets, such as exchange rate or money growth rate. Experience of other countries that have adopted inflation targeting as a monetary framework reveals that the success of the policy depends on not only the transparency of the operation but also on the budgetary discipline. Indeed, the central banks that have become more transparent, more independent, more coherent, and more accountable and more credible have been more successful. The controversy among economists on the expenses of inflation targeting has attained particular attention during the past decades .While opponents believe that inflation targeting takes place at the expense of output shortfalls (Cechetti and Ehrmann 1999), proponents (Mishkin 2000, Jonas and Mishkin 2003) believe that inflation targeting promotes investment and economic growth. This paper tries to address the question of whether the performance of inflation targeting in Iran has been successful. Based on a monetary model, using exogenous variables such as official exchange rate, budget deficit, foreign exchange obligation account, and balance of payments, the results suggest that the effects of inflation targeting on the real output is trivial, supporting the natural rate hypothesis.